2022
DOI: 10.1088/1755-1315/1093/1/012018
|View full text |Cite
|
Sign up to set email alerts
|

Nutrients in streams draining the different types of wetlands in Western Siberian Plain

Abstract: Two second order streams were compared to test the influence of peatbog type (minerotrophic vs. oligotrophic) on dissolved nutrient composition and dynamics during several hydrologic years. A significant spatio-temporal variation in the concentration of nutrients in the channel runoff is shown. It depends on the catchment characteristics and the hydrological period of the year. In general, the concentrations of phosphates, nitrates and nitrites are lower in the stream draining an area dominated by a minerotrop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 23 publications
(27 reference statements)
1
1
0
Order By: Relevance
“…The increased concentrations of major elements in the Klyuch River are probably determined by the smaller peatland-dominated area (about 77%) and the removal of substances from the catchment area occupied by mineral soils or ion-rich groundwater supply. Similar findings were made by (Tokareva et al 2022), whose research in the Yenisei River basin demonstrated that streams draining basins with a higher number of pristine ombrotrophic bogs (atmosphere-fed bogs) receive more atmospheric precipitation and have ion-poor runoff.…”
Section: Stream Water Chemistrysupporting
confidence: 82%
See 1 more Smart Citation
“…The increased concentrations of major elements in the Klyuch River are probably determined by the smaller peatland-dominated area (about 77%) and the removal of substances from the catchment area occupied by mineral soils or ion-rich groundwater supply. Similar findings were made by (Tokareva et al 2022), whose research in the Yenisei River basin demonstrated that streams draining basins with a higher number of pristine ombrotrophic bogs (atmosphere-fed bogs) receive more atmospheric precipitation and have ion-poor runoff.…”
Section: Stream Water Chemistrysupporting
confidence: 82%
“…On the contrary, the stream water pH in the drained part of the GVM was lower, which is determined by higher concentrations of DOC resulting from the decomposition of peat layers due to intensive drainage. Studies conducted in the Yenisei River basin (Tokareva et al 2022) also showed lower pH values and elevated concentrations of NH + 4 in stream water chemistry due to the input of highly acidic organic-rich solutes from a pristine peatland area within the basin and specific biogeochemical processes occurring directly in the stream channel.…”
Section: Stream Water Chemistrymentioning
confidence: 99%